The Effect of Green Color Breathing TherapyTowards Reduction of Stress Levels In Hemodialized Patients - Didik Prasetyo Suli; Nur Aini; Yoyok Bekti Prasetyo (Jurnal Keperawatan, 2019)
Hemodialysis therapy is a lifelong therapy for the patient. One therapy that can be used in lowering stress levels and not yet widely used in Indonesia is color therapy (chromotherapy). The research design was quasi experimental with a pre-post test with control group design. The total sample of 12 intervention groups and 13 control groups was taken by purposive sampling technique. The study was conducted in March 2017 at Dr. Soepraoen Malang Hospital. The variables observed were a decrease in stress levels using the DASS questionnaire. Data were analyzed by the Mann-Whitney test. The results showed that at pretest the majority of the intervention groups were at moderate stress levels of 5 people (41,7%), while in the control group 8 people (61,5%). After posttest the stress level in the intervention group fell to normal 8 people (66,7%) while in the control group it remained. The results of statistical tests obtained p value 0.001 < α 0.05 so it can be concluded that there is an effect of giving green color breathing therapy to decrease stress levels. Green color affects the central nervous system by using the retinohypothalamic tract as the main pathway of the color transmission mechanism to the limbic system and the endocrine system, so it will provide a calming effect, cause a sense of comfort, and reduce stress.